FTIR analysis of the interaction of arbutin with dimyristoyl phosphatidylcholine in anhydrous and hydrated states - Frías, María de los Ángeles (2006)
In this paper, the interaction of arbutin with dimyristoylphosphatidylcholine bilayers was studied by FTIR spectrometry. The results show that arbutin interacts in different extents with the phosphate and carbonyl groups of membranes in the gel state, the liquid crystalline state or subjected to osmotic stress. The effect, in the presence of water, on the antisymmetric stretching of the phosphate groups is qualitatively similar to that found with other molecules composed by a glucose moiety such as trehalose and sucrose. However, significant differences were found between these compounds and arbutin in the carbonyl region. Arbutin displaces the PO2- antisymmetric stretching to lower frequencies in lipids dispersed in water. This indicates strong hydrogen bonding. In contrast, in the solid state, this frequency increases. The effect on the carbonyl groups varies depending on the hydration state of the bilayer, which is achieved by changing the phase state of the bilayer or by osmotic stress. The hydrocarbon region is not affected by arbutin in the excess of water. However, symmetric and antisymmetric stretching of CH2 and CH3 are strongly affected in the dry state.